2023
DOI: 10.1182/blood.2022017661
|View full text |Cite
|
Sign up to set email alerts
|

Associations of clonal hematopoiesis with recurrent vascular events and death in patients with incident ischemic stroke

Abstract: Clonal hematopoiesis (CH) is common among older people and associated with an increased risk of atherosclerosis, inflammation, and shorter overall survival. Age and inflammation are major risk factors for ischemic stroke, yet the association of CH with risk of secondary vascular events and death is unknown. We investigated CH in peripheral blood DNA from 581 patients with first-ever ischemic stroke from the Prospective Cohort with Incident Stroke-Berlin study (PROSCIS-B) using error-corrected targeted sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…72,73 CH was also associated with increased white matter lesion load and proinflammatory profile among patients with ischemic stroke, and specifically patients with TET2 and PPM1D CH were associated with a higher risk for secondary vascular events and death after ischemic stroke. 73 DNMT3A CH has been associated with osteoporosis. 11 CH has inconsistently been associated with COVID-19 morbidity and mortality, [74][75][76] with associations existing with regards to increased severity of Clostridium difficile, and Streptococcus/Enterococcus infections.…”
Section: Ch and Other Medical Disordersmentioning
confidence: 94%
See 2 more Smart Citations
“…72,73 CH was also associated with increased white matter lesion load and proinflammatory profile among patients with ischemic stroke, and specifically patients with TET2 and PPM1D CH were associated with a higher risk for secondary vascular events and death after ischemic stroke. 73 DNMT3A CH has been associated with osteoporosis. 11 CH has inconsistently been associated with COVID-19 morbidity and mortality, [74][75][76] with associations existing with regards to increased severity of Clostridium difficile, and Streptococcus/Enterococcus infections.…”
Section: Ch and Other Medical Disordersmentioning
confidence: 94%
“…CH has been associated with increased of stroke; TET2 CH is associated with both overall and ischemic stroke, while DNMT3A is associated with increased risk of hemorrhagic stroke 72,73 . CH was also associated with increased white matter lesion load and proinflammatory profile among patients with ischemic stroke, and specifically patients with TET2 and PPM1D CH were associated with a higher risk for secondary vascular events and death after ischemic stroke 73 . DNMT3A CH has been associated with osteoporosis 11 .…”
Section: Ch and Other Medical Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently believed that CSF may be related to factors such as inflammation, decreased vascular endothelial function, and abnormal microvascular reserve function [ 4 , 7 , 8 , 9 , 10 , 11 ]. Numerous studies have demonstrated that inflammation plays an important role in the occurrence and development of cardiovascular and microvascular diseases [ 12 , 13 , 14 ]. Nevertheless, the role of inflammation in the occurrence and development of CSF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…CH has been recognized as a premalignant state predisposing to hematological malignancies [5,6]. Moreover, CH also confers risks for non-hematological diseases, such as coronary heart disease and rheumatoid arthritis [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%